2008
DOI: 10.1093/ndt/gfn388
|View full text |Cite
|
Sign up to set email alerts
|

The role of macrophage in the pathogenesis of chronic cyclosporine-induced nephropathy

Abstract: Thus, infiltrating macrophages were involved in both nonimmunologic and immunologic injury and led to apoptotic cell death in this rat model of chronic CsA nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 44 publications
1
24
0
2
Order By: Relevance
“…Cyclosporine nephrotoxicity is, in part, caused by oxidative stress, and urinary 8-hydroxydeoxygu anosine levels are increased by cyclosporine. [9][10][11] This is consistent with the present finding that rCoQ10, a strong antioxidant, may be protective against the nephrotoxic adverse effects of cyclosporine (Table 1). Several previous studies had suggested that cyclosporine nephrotoxicity may be improved or prevented by antioxidants.…”
Section: Discussionsupporting
confidence: 92%
“…Cyclosporine nephrotoxicity is, in part, caused by oxidative stress, and urinary 8-hydroxydeoxygu anosine levels are increased by cyclosporine. [9][10][11] This is consistent with the present finding that rCoQ10, a strong antioxidant, may be protective against the nephrotoxic adverse effects of cyclosporine (Table 1). Several previous studies had suggested that cyclosporine nephrotoxicity may be improved or prevented by antioxidants.…”
Section: Discussionsupporting
confidence: 92%
“…Practically, depletion of macrophages using liposome-encapsulated clodronate significantly decreased CsA-induced renal dysfunction and fibrosis. 23 Therefore, we investigated whether DPP IV inhibition affects TAC-induced macrophage infiltration and inflammatory factors. Many studies have demonstrated that DPP IV inhibitors inhibit the production of inflammatory cytokines and the activation of the nuclear factor-κB, suggesting that it has an anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…We previously clearly demonstrated that depletion of macrophages, the major infiltrating inflammatory cell type in chronic CsA nephropathy, using liposome-encapsulated clodronate, decreased CsA-induced inflammation, fibrosis, apoptotic cell death and oxidative injury [14]. Therefore, we investigated whether KRG treatment affects CsA-induced macrophage infiltration and inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…The high level of oxidative stress induced by chronic CsA administration causes structural and functional kidney impairment because short- and long-term CsA treatment induces free radical species in the kidney, causing apoptotic and autophagic cell death [1,12,14]. In this study, we found that the expression of the oxidative stress marker, 8-OHdG, was increased in the 24-hour urine and renal tubules and in the culture media of CsA-treated cells, but that co-treatment with KRG decreased these parameters.…”
Section: Discussionmentioning
confidence: 99%